Preparation of Nanomaterial Thin Film as Saturable Absorber - Tuman Aliwi, Tabarak sadiq; Jabir Tarad, Noor Alaa; muttalib hafez, Elaf abdul; Abboud Qasim, Fatima Bashar; Awad Hadi, Tabark Abbas; abd alhassan, Jumana rafeek jafer; Abed Alrasool, Mariem Amer Namaa (American Journal of Botany and Bioengineering, 2025)
In this project, an Erbium doped fiber laser (EDFL) with passive Q-switching was created employing saturable absorber (SA) composed of Zirconium Dioxide-8Ytria nanomaterial. The fabrication of SA involved the drop-casting method, with polyvinyl alcohol (PVA). SA materials were characterized using different techniques to determine their Optical and physical spectroscopic analyses. Their crystalline structure was examined using X-ray diffraction (XRD) analysis, the morphological arrangement was measured by Scanning Electron Microscope (SEM), and the optical characteristics were found using UV- Vis Spectrophotometer. By integrating the proposed SAs in the all-fiber ring cavity, Q-switched pulse operation generated directly using an EDF as an active medium. a stable Q-switched regime with the maximal pulse repetition rate of 52.5 kHz, the shortest pulse width of 10.5 μs, and maximum average output power up to 151.7 µW were attained at a maximum available pump power of 280 mW.